2015
DOI: 10.1007/s10072-015-2317-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum glial fibrillary acidic protein test as a promising tool for intracerebral hemorrhage diagnosis in Chinese patients and prediction of the short-term functional outcomes

Abstract: The objective of this study was to explore the efficacy of glial fibrillary acidic protein (GFAP) in differentiating intracerebral hemorrhage (ICH) from ischemic stroke (IS). Suspicious patients of acute stroke were screened and finally diagnosed by computed tomography and magnetic resonance imaging. Blood samples were collected within 2-6 h after onset of symptoms, and serum GFAP level was determined by ELISA assay. The functional outcome for the patients was determined by modified Rankin Scale (mRS) 90 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
0
30
1
4
Order By: Relevance
“…Figure gives the schematic representation of the systematic review. After scanning through the title and abstract of each article, 37 full text studies were assessed for eligibility; out of which 18 articles from 2004 to 2017 were found relevant and were included in our systematic review. The review highlights the role of 10 single biomarkers (ApoC‐1, ApoC‐III, GFAP, RBP4, hs‐CRP, APC‐PCI, Apo‐AI, Paraoxonase‐1, BNP, S100B) and seven panels consisting of several different biomarkers for distinguishing the two stroke types.…”
Section: Resultsmentioning
confidence: 99%
“…Figure gives the schematic representation of the systematic review. After scanning through the title and abstract of each article, 37 full text studies were assessed for eligibility; out of which 18 articles from 2004 to 2017 were found relevant and were included in our systematic review. The review highlights the role of 10 single biomarkers (ApoC‐1, ApoC‐III, GFAP, RBP4, hs‐CRP, APC‐PCI, Apo‐AI, Paraoxonase‐1, BNP, S100B) and seven panels consisting of several different biomarkers for distinguishing the two stroke types.…”
Section: Resultsmentioning
confidence: 99%
“…A blood GFAP level at the cut point of 0.7 ng/mL yielded an AUC of 0.901 (95% CI 0.828-0.950) with high sensitivity (86.0%) and specificity (76.9%) to differentiate ICH from ischemic stroke. [ 47 ] In addition, in the ICH group, a significant correlation was observed between GFAP levels and neurological deficits assessed by NIHSS, and between GFAP levels and hemorrhage volume, and the highest GFAP levels were predictive of poor short-term functional outcomes. [ 47 ] Furthermore, a recent study suggested that GFAP used in combination with NR2 can differentiate between ischemic stroke and ICH at a time point extended to 12 h after the ictus with a sensitivity of 94% and specificity of 91%.…”
Section: Use Of Blood Glial Fibrillary Acidic Protein Levels For Earlmentioning
confidence: 99%
“…[ 47 ] In addition, in the ICH group, a significant correlation was observed between GFAP levels and neurological deficits assessed by NIHSS, and between GFAP levels and hemorrhage volume, and the highest GFAP levels were predictive of poor short-term functional outcomes. [ 47 ] Furthermore, a recent study suggested that GFAP used in combination with NR2 can differentiate between ischemic stroke and ICH at a time point extended to 12 h after the ictus with a sensitivity of 94% and specificity of 91%. [ 46 ] Another study showed that plasma concentrations of retinol binding protein 4 and GFAP at concentrations >61 μg/mL and <0.07 ng/mL, respectively, demonstrated 100% specificity, and these biomarkers might be independent predictors to discriminate stroke subtype, improving discrimination by 29% ( P < 0.0001).…”
Section: Use Of Blood Glial Fibrillary Acidic Protein Levels For Earlmentioning
confidence: 99%
“…Biomarkers, GFAP, CRP, cortisol and glucose, are all unbiased measures that have been used to predict post-hospital (30-90 days) mortality [3][4][5] rather than more acute, in-hospital outcomes. Since 8-10% of stroke patients will die in-hospital [1,2] and 84% of hospice patients die with a median length of stay of 13 days [35] we felt that predicting early mortality was an important event.…”
Section: Discussionmentioning
confidence: 99%
“…Several stroke biomarkers have been used to predict 30-90 day outcomes based on serum levels of glial fibrillary acidic protein (GFAP), C-reactive protein (CRP), cortisol and glucose [3][4][5]. Only one study reported predictive values using in-hospital death as an end-point [6].…”
Section: Introductionmentioning
confidence: 99%